IMPLIKASI HUKUM PEMBEBANAN HAK TANGGUNGAN ATAS TANAH HAK GUNA BANGUNAN DI ATAS TANAH HAK PENGELOLAAN YANG IJIN PEMANFAATAN TANAHNYA DICABUT OLEH GUBERNUR - Saraswati, A.A.Ayu Ray; Atmadja, I Dewa Gede; Suyatna, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 2 (2016), 2016)
Governor as the head of the province has the authority to regulate the allocation and use of assets held by the provincial government, including land management rights. The purpose of management rights titled land is to be given to a third party. This provision is based on the Decree of the Governor in form of land utilization permit. Furthermore, over that given land, the rights of land can be applied above it, for example Building Right Title. Problem that occur is if the Governor as concessionaires strip the utilization permit that has been granted, as in the case of Management Rights Titled Land No.2 with the Building Right Title Land No. 80 on behalf of PT. Abdi Persada Nusantara in Kesiman Petilan Village, Denpasar. What about the legal status of land rights that existed on the management rights titled land and the legal consequences of the burdening the liability right to management rights titled land after the revocation of the land utilization permit. This type of research in this thesis is a normative legal research, the research that seek answers by examining the problems of legal materials and the use of primary and secondary theoretical foundation as one of the characteristics of a normative study. The approach used in this study is the Regulation Approach, Legal Concepts Analysis Approach and the Case Approach, furthermore the discussion done by descriptive analysis way by describing and analyzing the results obtained from the legal materials, systematically arranged so that the conclusion can be obtained. Result of study of the prooblems studied is the legal status of land rights on management rights titled land that it’s utilization permit has been stripped by the concessionaires became abolished. Abolishment of the land rights led to liability rights does not lead to the abolishment of the secured debt. Receivables creditors still there, but no longer as claims that guaranteed specifically by the special position of the creditor (lender preferred)
Keywords: Legal Consequeces, Building Rights Tittle, Management Rights, Land Utilization Permits, Governor.